The relevance of tricuspid regurgitation in patients undergoing percutaneous treatment of mitral regurgitation. Issue 6 (3rd February 2022) - Brunner, Stephanie; Wolfrum, Mathias; Moccetti, Federico; Stämpfli, Simon F.; Attinger‐Toller, Adrian; Bossard, Matthias; Matt, Peter; Cuculi, Florim; Kobza, Richard; Toggweiler, Stefan
Abstract: Objectives:  Investigate the impact of concomitant tricuspid regurgitation (TR) on clinical outcomes during long‐term follow‐up in patients undergoing percutaneous treatment of mitral regurgitation (MR) with the MitraClip system. Background: Patients undergoing mitral repair using the MitraClip frequently present with concomitant TR. It is uncertain how the presence of TR impacts the long‐term outcomes of such patients. Methods: We analyzed consecutive patients with MitraClip implantation from the prospective MitraSwiss registry. Endpoints were all‐cause mortality, hospitalization for heart failure, and the composite endpoint of the two. Results: We enrolled 177 patients (mean age 76 ± 9 years, 37% female). Acute procedural success was achieved in 149 (84%). Concomitant moderate or severe TR was present in 31% at baseline and 32% before discharge. After a median follow‐up of 1103 days (IQR: 555–1766 days), 70 (40%) of patients had died, and 34 (19%) were hospitalized for heart failure. In multivariable analysis, TR at baseline was associated with an increase in all‐cause mortality (HR: 2.34, 95% CI: 1.36–4.03, p  < 0.01), hospitalization for heart failure (HR: 3.19, 95% CI: 1.37–7.41, p  = 0.01), and the composite endpoint (HR: 2.00, 95% CI: 1.19−3.36, p  = 0.01). Conclusion: Despite treatment of MR, TR did not improve in most patients. The presence of relevant TR at baseline was associated with reduced survival and higher rates of hospitalization for heart failure. More research is needed to understand the causal role of TR in such patients and to investigate if simultaneous treatment of concomitant TR may improve prognosis in patients undergoing percutaneous treatment of MR.